Ethical design in social media: Assessing the main performance measurements of user online behavior modification - Saura, José Ramón; Palacios-Marqués, Daniel; Iturricha-Fernández, Agustín (Journal of business research, 2021)
•The indicators used by social networks to increase user engagement are questioned.•10 performance measurements and 4 ethical design measurements are defined.•We discuss the links between online ethical design and surveillance capitalism.•Indicators that could generate user online behavior modification are criticized.•Social networks business models based on user engagement are analyzed. The growing use of social networks has led to the emergence of ethical and privacy concerns regarding the management of user data and how social networks train algorithms for economic purposes to organize the content shown to users. In this context, the present study aims to define and identify (i) the main concepts and (ii) performance measurements that social networks use to increase user engagement and modify user online behavior from the perspective of ethical design and surveillance capitalism in social media. Since previous research on this issue is scarce, this study bridges this gap in the literature by developing a Systematic Literature Review (SLR) of major scientific contributions made so far in this research area. We identify a total of 10 performance measurements and 4 ethical design measurements used by social media companies to increase user engagement and to achieve user behavior modification online, at times without users’ awareness about this effect. Furthermore, we critically analyze the identified 14 indicators, as previous research suggests that these indicators can generate addiction and modification of user behavior and feelings. The paper concludes with a discussion of important theoretical and practical implications of ethical design in social media for further research; we also question the economic approaches proposed in the business models of digital and social media platforms.